Stadium renderings - Unidentified artist (Colorado State University. Libraries, 2016)
Artists' rendering of the proposed CSU stadium.
Color image of artists' rendering of the proposed CSU stadum currently under construction. Shows the attached buildings, stadium seating, and partial view of the football field.
Keywords: new CSU football stadium; Colorado State University; buildings